Graduate Students' Awareness Regarding the Internet of Things Technology and Its Uses in the Educational Process at the University of Jordan - Abu Robe, Jehad Abdullah; Al-Btoush, Razan Salem; Arouri , Yousef Mhmoud (Dirasat: Educational Sciences, 2023)
Objectives: This study aims to assess the awareness level of postgraduate students at the University of Jordan regarding the Internet of Things (IoT) technology and its applications in the educational process. Additionally, it examines the impact of program level, school classification, and age on the awareness level. Methods: The study adopts a descriptive survey method, employing a questionnaire distributed among a stratified random sample of 362 postgraduate students registered for the second semester of 2021/2022. Results: The findings indicate a moderate level of awareness among students regarding the Internet of Things technology and its applications in the educational process. No statistically significant differences were observed in the awareness estimates among the study sample based on program level. However, statistically significant differences were found based on school classification, favoring scientific schools, as well as based on age, favoring individuals aged 40 years or younger. Conclusions: To enhance students' awareness, particularly among those in humanities schools and older age groups, it is recommended to conduct training workshops focusing on the Internet of Things technology services in the educational process.